Investigation on Furan Levels in Pressure-Cooked Foods - Adriana P. Arisseto; Eduardo Vicente; Maria Cecília F. Toledo (International Journal of Food Science)
Furan is a food processing contaminant classified as possibly carcinogenic to humans. As the occurrence of furan has been reported in a variety of foods processed in sealed containers, the objective of this work was to investigate if the contaminant can be found in home-cooked foods prepared in a pressure cooker. For that, several foods including beans, soy beans, whole rice, beef, pork, potato, and cassava were pressure-cooked and analyzed for the furan content by gas chromatography coupled to mass spectrometry preceded by a headspace solid phase microextraction (HS-SPME-GC/MS). Furan was not found above the limit of quantification in the pressure-cooked samples. No furan has either been found in reheated samples after 24 hours under cold storage. Although levels up to 173 μg/kg were already reported for commercial canned/jarred foods, it seems that the cooking in a pressure cooker may not represent a concern in relation to the occurrence of furan in foods.